1993
DOI: 10.1136/jnnp.56.4.369
|View full text |Cite
|
Sign up to set email alerts
|

Focal electroencephalographic abnormalities and computerised tomography findings in children with seizures.

Abstract: A persistent focal abnormality was observed in 157 (16%) electroencephalograms undertaken in 964 consecutive children with epileptic and non-epileptic seizures seen over one year. CT head scans were performed in 121 (77%) of the 157 children with a focus on the EEG; 26 (21%) showed an abnormality, and 21 (81%) of the abnormalities were localised. There was no difference in the proportion of abnormal scans associated with a delta or slow wave focus compared with a spike or sharp wave focus. An abnormal scan was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…13,14 Similar to our finding, in study by Gibbs et al, atrophy was the most common CT scan abnormality that was found in 9.0% of children suffering from seizure. 8 CT revealed generalized atrophy in 6.0% and focal atrophy in 7.0% children in study by Bachman et al 4 NCC was the second most common abnormality detected by CT scan in our study.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…13,14 Similar to our finding, in study by Gibbs et al, atrophy was the most common CT scan abnormality that was found in 9.0% of children suffering from seizure. 8 CT revealed generalized atrophy in 6.0% and focal atrophy in 7.0% children in study by Bachman et al 4 NCC was the second most common abnormality detected by CT scan in our study.…”
Section: Discussionsupporting
confidence: 54%
“…4,[8][9][10] In studies done in children, the positivity rate of CT scan were variable, ranging from 21.0% to 41.7% in developed countries and as high as 70.0% in Indian subcontinent. The positivity rate of CT scan was 21.0% out of investigated cases in study by Gibbs et al, 8 41.7% in study by Ladurner et al, 11 30.0 % in study by Bachman et al, 4 and 39.5 % in study by Al-Sulaiman et al 12 This wide variation in positivity rate of CT scan might be because of bias in selection of cases for ordering CT scan. Another reason could be high prevalence of neurocysticercosis (NCC) and perinatal brain injury in developing world, especially Indian subcontinent.…”
Section: Discussionmentioning
confidence: 99%
“…10 The yield of abnormalities is highest in children with partial seizures who have focal abnormalities on EEG and/or neurological examination, and in neonates irrespective of seizure type, neurological examination, or EEG findings 911 12 One child in this survey presented at the age of 8 years with focal seizures and had a cystic area on computed tomography (CT) at presentation. Repeat CT six years later because of intractable partial seizures and unilateral clumsiness led to excision of this cystic lesion, which was found to be a gangliocytoma.…”
Section: Discussionmentioning
confidence: 95%
“…[3] Only a few studies have addressed the radiological evaluation of children with partial seizures [Table 5]. There is higher incidence of normal CT scan of brain (50-79%) in studies from the developed countries[81018] when compared to studies from India (37-76%). [11920] Lagenstein et al .…”
Section: Discussionmentioning
confidence: 99%